Kinerja Lembaga Penyiaran Publik Radio Republik Indonesia (Studi Tentang Kinerja Pegawai di Lembaga Penyiaran Publik RRI Manado) - Makawimbang, Halmintje; Rumapea, Patar; Ruru, Joorie (Sam Ratulangi University, 2015)
Abstract : This research aims to analyze the performance of a Public Broadcasting Institution theradio Indonesia Republic in Manado. Public Broadcasting Institution the radio Indonesia Republic inManado as a government bureaucracy is the one work unit in North Sulawesi. Public BroadcastingInstitution the radio Indonesia Republic in Manado is institutions that convey information as well as news –actual and reliable news as well as provide entertainment to the community particularly the city of Manado.To carry out its work, Public Broadcasting has a function a. Deliver/broadcast news and Information toactual and reliable, providing wholesome Entertainment to the community. The central problem in the studybased on the pre survey, for example, the protection of the rights of women workers, safety (safety securitywork) and also a guarantee against social workers. Qualifying employees in particular HR limitations ofEchelon IV also become constraints in the implementation of tasks and jobs. In addition still lack of trainingtrainingis to support the technical skill employees create a work to be hampered due to the lack of technicalknowledge of employees in carrying out his job. Therefore, in a situation like this, the head of Department orhead of the need to conduct performance assessment to review the extent to which employee performance andevaluate the effectiveness of the deficiencies contained therein so that action can be taken as soon as possibleto resolve the issue.In this study the author uses a quantitative approach. quantitative data processing-data that isobtained from the location of the research with data collection techniques: study library and study field, asfor Informants in this study was the assessment of officials is tops on Public Broadcasters, among them headof the radio Indonesia Republic in Manado Station, the head of the field and the head section.The results of this research are generally speaking the performance of employees in the PublicBroadcasting Institution the radio Indonesia Republic in Manado can be said to have good, based on thefinal value of each employee's performance with Employees Working Objectives values accumulate (SKP)and overall work so that Behavior can be inferred to be on the level of